Co-Delivery of Curcumin and Paclitaxel by “Core-Shell” Targeting Amphiphilic Copolymer to Reverse Resistance in the Treatment of Ovarian Cancer - Zhao MD; Li JQ; Chen FY; Dong W; Wen LJ; Fei WD; Zhang X; Yang PL; Zhang XM; Zheng CH (International Journal of Nanomedicine, 2019)
Meng-Dan Zhao,1 Jun-Qin Li,2 Feng-Ying Chen,1 Wei Dong,3 Li-Juan Wen,4 Wei-Dong Fei,1 Xiao Zhang,1 Pei-Lei Yang,1 Xin-Mei Zhang,2 Cai-Hong Zheng1 1Department of Pharmacy, Women’s Hospital, Zhejiang University School of Medicine, Hangzhou 310006, People’s Republic of China; 2Department of Gynecology, Women’s Hospital, Zhejiang University School of Medicine, Hangzhou 310006, People’s Republic of China; 3Department of Neurology, The Affiliated Yangming Hospital of Ningbo University, Yuyao People’s Hospital of Zhejiang Province, Yuyao 315400, Zhejiang, People’s Republic of China; 4Institute of Pharmaceutics, College of Pharmaceutical Science, Zhejiang University, Hangzhou 310058, People’s Republic of ChinaCorrespondence: Xin-Mei Zhang; Cai-Hong Zheng Email zhangxinm@zju.edu.cn; chzheng@zju.edu.cnBackground: Ovarian cancer is a common malignancy in the female reproductive system with a high mortality rate. The most important reason is multidrug resistance (MDR) of cancer chemotherapy. To reduce side effects, reverse resistance and improve efficacy for the treatment of ovarian cancer, a “core-shell” polymeric nanoparticle-mediated curcumin and paclitaxel co-delivery platform was designed.Methods: Nuclear magnetic resonance confirmed the successful grafting of polyethylenimine (PEI) and stearic acid (SA) (PEI-SA), which is designed as a mother core for transport carrier. Then, PEI-SA was modified with hyaluronic acid (HA) and physicochemical properties were examined. To understand the regulatory mechanism of resistance and measure the anti-tumor efficacy of the treatments, cytotoxicity assay, cellular uptake, P-glycoprotein (P-gp) expression and migration experiment of ovarian cancer cells were performed. In addition, adverse reactions of nanoformulation to the reproductive system were examined.Results: HA-modified drug-loaded PEI-SA had a narrow size of about 189 nm in diameters, and the particle size was suitable for endocytosis. The nanocarrier could target specifically to CD44 receptor on the ovarian cancer cell membrane. Co-delivery of curcumin and paclitaxel by the nanocarriers exerts synergistic anti-ovarian cancer effects on chemosensitive human ovarian cancer cells (SKOV3) and multi-drug resistant variant (SKOV3-TR30) in vitro, and it also shows a good anti-tumor effect in ovarian tumor-bearing nude mice. The mechanism of reversing drug resistance may be that the nanoparticles inhibit the efflux of P-gp, inhibit the migration of tumor cells, and curcumin synergistically reverses the resistance of PTX to increase antitumor activity. It is worth noting that the treatment did not cause significant toxicity to the uterus and ovaries with the observation of macroscopic and microscopic.Conclusion: This special structure of targeting nanoparticles co-delivery with the curcumin and paclitaxel can increase the anti-tumor efficacy without increasing the adverse reactions as a promising strategy for therapy ovarian cancer.Keywords: co-delivery, curcumin, reverse resistance, paclitaxel, ovarian cancer, adverse reactions